Study the Behavior of Asphalt Cement Modified by Different Types of Nanocarbons - Sheelan A. Ahmed; Hirsh M. Majid (Civil Engineering Journal, 2026)
Nanocarbon application as an asphalt cement modifier has revealed improved and satisfactory results in the rheological properties of modified asphalt cement. All previous studies examined the effect of one or more nanocarbons, regardless of the effect of nanosized and nanoparticle shapes on these results. Therefore, this study is meant to contribute to knowledge on the novelty of the effect of nanocarbon particle shapes for the modification of asphalt cement. For this purpose, three distinct nanocarbon forms—nano graphite (NGR) powder, multiwalled carbon nanotubes (MWCNTs), and nano carbon black powder (NCB)—are employed to modify asphalt cement, while restricting their nano dimension to small ranges (20–40 nm), and added with various dosage percentages (1.5%, 3%, 4.5%, and 6% by weight of the binder). They were evaluated utilizing Field Emission Scanning Electron Microscope (FESEM), Fourier transform infrared (FTIR), rotational viscosity (RV), and Dynamic Shear Rheometer (DSR). The results showed that the performance of asphalt cement was enhanced by all varieties of nanocarbons employed in this investigation, and increasing the percentage of nanocarbons utilized to modify the asphalt also had a favorable effect. However, when comparing the performance of utilizing these different types of nanocarbons, MWCNTs performed best in terms of dispersion within the asphalt matrix, decreasing asphalt oxidation, reducing sensitivity to temperature changes, improving rheological properties, and increasing resistance to permanent deformation.